Intensification of future subsurface marine heatwaves in an eddy-resolving model - Xiuwen Guo; Yang Gao; Shaoqing Zhang; Wenju Cai; Deliang Chen; L. Ruby Leung; Jakob Zscheischler; Luanne Thompson; Kristen Davis; Binglin Qu; Huiwang Gao; Lixin Wu (Nature Communications)
Abstract A shift in depth range enables marine organisms to adapt to marine heatwaves (MHWs). Subsurface MHWs could limit this pathway, yet their response to climate warming remains unclear. Here, using an eddy-resolving Earth system model forced under a high emission scenario, we project a robust global increase in subsurface MHWs driven by rising subsurface mean temperatures and enhanced temperature variability. Historically, maximum MHW intensity occurs around 100 m depth, which shifts to the faster-warming surface under greenhouse warming. However, removing the long-term warming trend yields an increase in subsurface MHW intensity and annual days greater than that at the surface, especially in large marine ecosystem regions, primarily due to increased variability. Additionally, days of the surface and subsurface concurrent event increase ten times more than those of individual events. Our study highlights a heightened threat to marine organisms under global warming, as the increased subsurface heatwaves reduce their refuge options.